Pembacaan Heuristik dan Hermeneutik Ferdinand De Saussure Symbol Ketimpangan Gender Dalam Novel Perempuan di Titik Nol - Tjalau, Cutri; Gazali, Indriani; Sarif, Suharia (Assuthur: Jurnal Pendidikan Bahasa Arab, 2023)
The novel is an imitation of the life of the society around it. Literary works such as novels are cultural products that hold value as a means of communication for conveying ideas in the form of texts or stories, providing thousands of meanings within, especially in discussing the reality of social life. "Woman at Point Zero" is a novel by Nawal El Saadawi that serves as a form of critique directed towards the culture ingrained in her country. Feminist ideas are encapsulated within it, prompting researchers to seek signs and symbols of gender inequality arising from biological differences seen through social, political, and cultural aspects. Employing heuristic and hermeneutic readings with Ferdinand de Saussure's semiotic theory, four quotations about symbols of gender inequality stemming from biological differences are derived from the social aspect, two quotations from the political aspect, and two quotations from the economic aspect